Development of Surgical and Visualization Procedures to Analyze Vasculatures by Mouse Tail Edema Model - Shinji Kumegawa (BMC, 2021)
Abstract Background Because of the high frequency of chronic edema formation in the current “aged” society, analyses and detailed observation of post-surgical edema are getting more required. Post-surgical examination of the dynamic vasculature including L.V. (Lymphatic Vasculature) to monitor edema formation has not been efficiently performed. Hence, procedures for investigating such vasculature are essential. By inserting transparent sheet into the cutaneous layer of mouse tails as a novel surgery model (the T ail E dema by S ilicone sheet mediated T ransparency protocol; TEST), the novel procedures are introduced and analyzed by series of histological analyses including video-based L.V. observation and 3D histological reconstruction of vasculatures in mouse tails. Results The dynamic generation of post-surgical main and fine (neo) L.V. connective structure during the edematous recovery process was visualized by series of studies with a novel surgery model. Snapshot images taken from live binocular image recording for TEST samples suggested the presence of main and elongating fine (neo) L.V. structure. After the ligation of L.V., the enlargement of main L.V. was confirmed. In the case of light sheet fluorescence microscopy (LSFM) observation, such L.V. connections were also suggested by using transparent 3D samples. Finally, the generation of neo blood vessels particularly in the region adjacent to the silicone sheet and the operated boundary region was suggested in 3D reconstruction images. However, direct detection of elongating fine (neo) L.V. was not suitable for analysis by such LSFM and 3D reconstruction procedures. Thus, such methods utilizing fixed tissues are appropriate for general observation for the operated region including of L.V. Conclusions The current surgical procedures and analysis on the post-surgical status are the first case to observe vasculatures in vivo with a transparent sheet. Systematic analyses including the FITC-dextran mediated snap shot images observation suggest the elongation of fine (neo) lymphatic vasculature. Post-surgical analyses including LSFM and 3D histological structural reconstruction, are suitable to reveal the fixed structures of blood and lymphatic vessels formation.